Infraestrutura portuária, memória e vida urbana : Porto de Vitória (Brasil) - Sorte, Nathália Spala (2016)
Changes in sea transport and technological advances have made port facilities go through profound changes, not only in physical form, but above all in relation to the city, especially with its central and historic areas. This dissertation deals with the s